Special Endurance And Its Relation To The Years Of Training Experience Of Middle Distance Sprinters - Field Study Of The Club Of Stars Of Athletics Hassi Bahbah - - Kadraoui, brahim; harbi, salim (Journal of Sport Science Technology and Physical Activities, 2019)
The study aimed at finding out the relationship between the special endurance and the years of training experience for the half-distance athletes for the athletics stars club Hassi Bah bah. The sample of the research was randomly selected from the Stars of Athletics Club as many as (14) Between (04) and (05) years, a series of physical tests were conducted as a data collection tool in this study. The results concluded that there was a statistically significant relationship between spécial endurance and the years of training experience for middle distance sprinters.